Tom Phillips’s illustrations for the Folio edition of Waiting for Godot - Claudia Parra; Peter James Harris (Ilha do Desterro)
In the light of the imagery associated with Samuel Beckett’s Waiting for Godot, in set designs, posters and book covers, the present article examines Tom Phillips’s  illustrations for the Folio Society edition of Waiting for Godot (2000). Considering that Phillips’s images embody a particular style in form and structure, functioning as pictorial elements recalling contexts, images and relations, we propose that the artist predicates his work on the premise that readers will have had previous contact with the play either in performance or as a text.